Thermal Tolerance and Host Plant Suitability of Bemisia tabaci MED (Gennadius) in Brazilian Legume Crops - de Lima Alvarez, Daniel [UNESP]; Hayashida, Rafael; Santos, Daniel Mariano [UNESP]; da Silva, Felipe Barreto; Müller, Cristiane; Krause-Sakate, Renate [UNESP]; Hoback, William Wyatt; de Oliveira, Regiane Cristina [UNESP] (MDPI, 2025)
The whitefly, Bemisia tabaci, is a complex of cryptic species that is a significant pest of different legume hosts that inhabits various regions worldwide with diverse climates and characteristics. Its adaptability is often facilitated by the insect’s microbiome, which can contribute to both the metabolism of host plant secondary compounds and insecticide resistance. The most relevant biotypes in Brazil are Middle East-Asia Minor 1 (MEAM1) and Mediterranean (MED), because of their ability to damage different hosts. Although MEAM1 is the prevalent species in Brazil, MED has great potential to spread, and there is little current knowledge about the biology of this biotype in the country. Therefore, the objective of this study was to evaluate the development and viability of MED on two legumes, soybean and common bean, alongside cotton, bell pepper, and tomato, at temperatures of 20 °C, 23 °C, 26 °C, 29 °C, 32 °C, and 35 °C and characterize the composition of its endosymbionts. Temperatures between 23 °C and 32 °C were the most suitable for B. tabaci MED development and viability across all tested host plants, whereas 35 °C proved harmful for insects reared on legumes. We observed a temperature threshold (°C) and thermal constant (degree-days) that varied according to the host plant, ranging from 9.81 °C and 384.62 for soybean to 11.17 °C and 333.33 for bell pepper, respectively. The main endosymbionts were in a ratio of 80% Hamiltonella and 20% Cardinium. These results allow the future mapping of risk for the MED biotype on different host plants in Brazil and elsewhere in South America.